Analysis of Factors Causing Delays in MCT Sealing Block Handi Block HB40 Material Distribution for Offshore Fabrication Using Fishbone Diagram - Setyananda Ikhsan Al-Mishkey; Hery Irwan (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
Material distribution delays can disrupt offshore fabrication because production activities depend on the timely availability of specialized materials. This study aims to identify the root causes of delays in the distribution of MCT Sealing Block Type Handi Block HB40 materials using Root Cause Analysis (RCA) through the Fishbone Diagram. A descriptive qualitative case study approach was employed. Data were collected through direct observations of material planning, procurement, shipment, monitoring, and receiving processes, supported by document reviews and relevant literature. The analysis included problem identification, cause classification, Fishbone Diagram development, and interpretation of causal relationships. The results indicate that distribution delays are influenced by five interrelated factors: Man (People), Method, Material, Machine/Facilities, and Environment. The major causes include inadequate coordination, insufficient integration between distribution planning and fabrication schedules, uncertain supplier lead times, limited shipment tracking, and weather and multimodal transportation constraints. The Fishbone Diagram demonstrates that distribution delays result from the interaction of these factors rather than a single dominant cause. The findings provide a systematic framework for improving offshore material distribution by strengthening cross-functional coordination, integrating planning with fabrication schedules, improving supplier lead-time management, and enhancing shipment monitoring systems.